Komunikasi Verbal yang Dilakukan oleh Jubir Covid 19 di Indonesia - Qolbiya Sakinah; Chairiawaty (UPT Publikasi Ilmiah Unisba, 2021)
Abstract. Communication is a very basic thing in human life, even communication has become a phenomenon for the formation of a society or community that is integrated by information, where each individual in the community itself shares information (Information sharing) to achieve common goals. . In simple terms, communication can occur when there is a similarity between the message and the person receiving the message. In providing information for the task force to accelerate the handling of covid 19 in Indonesia, Achmad Yurianto gave a statement